(untitled) (Journal of the College of Education for Women, 2024)
The research aims to study the syntactic level and the semantic structure level in the story of Taloot and Goliath in the Holy Qur’an to demonstrate the graphic effect that these two levels perform in revealing the deep meanings of the text. Dealing with the Qur’anic text and trying to understand it correctly differs from other linguistic texts because of its distinctive linguistic value and its value in people’s hearts. The Holy Qur’an has a wonderful harmony between its words and its images, giving a great importance to the semantic signs, which has a close relationship in revealing the meaning and arriving at a correct reading consistent with the linguistic signs. The Qur’an has distinctively used the interrogative methods and its diverse tools in using the real interrogatives or the metaphorical ones, which gives the text semantic dimensions which contributes in defining the meaning and expressing it in a way gives the text a cognitive value that enlightens the mind of the recipient. It is known that semantic topics at their different levels are among the most important linguistic topics that have a close relationship in highlighting the meanings in the Qur’anic verses and explaining them accurately, without which it would not be possible to get a harmonious and acceptable guidance or a correct reading of the Qur’anic texts. The importance of context has emerged through verbal and moral clues inside or outside the text, such as the context of the situation and position, or the elements of time, place, the addressee, and the speaker related to it in interpreting the text, stating the purposes of the speech, and making the recipient understand a meaning that would not have existed without the significance of the context.